2008
DOI: 10.1155/2008/312753
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Onset of Cavitation in Automotive Torque Converters—Part II: A Generalized Model

Abstract: The objective of this investigation was to develop a dimensionless model for predicting the onset of cavitation in torque converters applicable to general converter designs. Dimensional analysis was applied to test results from a matrix of torque converters that ranged from populations comprised of strict geometric similitude to those with more relaxed similarities onto inclusion of all the torque converters tested. Stator torque thresholds at the onset of cavitation for the stall operating condition were expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 8 publications
0
18
0
1
Order By: Relevance
“…converters has been reported decades ago [8] [9], and continuous efforts have been put into the investigation and control of cavitation in torque converters [10].…”
Section: •3•mentioning
confidence: 99%
See 1 more Smart Citation
“…converters has been reported decades ago [8] [9], and continuous efforts have been put into the investigation and control of cavitation in torque converters [10].…”
Section: •3•mentioning
confidence: 99%
“…The microwave telemetry technique [11]and the nearfield acoustic test approach [12]were proposed to investigate cavitation phenomena in a series of torque converters. In another approach, Robinette et al tested a matrix of torque converters and developed a dimensionless model for predicting cavitation [13]. Reynolds measured the sound power level in torque converters over various speed ratios and developed a response surface model to estimate the sound power of a working torque converters [14].…”
Section: Figure 1 Schematic Diagram For a Typical Automotive Torque Cmentioning
confidence: 99%
“…A second order function was assumed for the RSM used in this investigation, which contains linear, quadratic and two factor interactions as used by [12]:…”
Section: Model Functionsmentioning
confidence: 99%
“…Liu et al [7][8] studied the influence of the stator blade shape on the cavitation process of a hydraulic torque converter and found that cavitation is directly related to the internal mass flow rate. Robinette et al [9][10][11] investigated the effects of torque converter design and operating conditions on the onset of cavitation during vehicle launch using a nearfield acoustical technique. From their numerical results, Dong et al [12] determined that the cavitation on the stator leading edge grew in size with increasing pump speed, resulting in severe performance degradation in the torque converter.…”
Section: Introduction mentioning
confidence: 99%